Description of Farmer Behavior Towards Pesticide Management in Piga Village, Soa Subdistrict, Ngada Regency - Maria Ermelinda Menge Bay; Muntasir -; Thadeus A.L Regaletha (Universitas Nusa Cendana, 2022)
Pesticides are toxic chemicals, so the behaviour of managing the use of pesticides must be adequately considered so as not to impact the health of farmers. This study described the behaviour of buying, mixing, spraying, securing used pesticides, storing pesticide residues and using PPE. This type of research was descriptive research with survey research methods. This research was located in Piga Village, Soa District, Ngada Regency, with a total sample of 89 farmers, taken by simple random sampling technique. The study results were analyzed descriptively and presented in tabular form. The results showed that all respondents had good behaviour in purchasing pesticides, 72,5% of respondents had lousy behaviour in mixing pesticides, all respondent farmers had good behaviour in spraying pesticides, all respondent farmers had poor behaviour in securing pesticides containers, 76,25 respondent farmers had poor behaviour in storing pesticides residue, and all respondent farmers have bad behaviour in the use of personal protective equipment (PPE) namely <5 types of personal protective equipment. Farmers should store pesticides in a particular place and not store them in rice warehouses. Also, farmers should provide a special place for the disposal of pesticide containers that have been used. Pesticide doses should be used under the rules, and farmers are expected to continually use personal protective equipment when working with pesticides.